Activity of tafasitamab in combination with rituximab in subtypes of aggressive lymphoma - Patra-Kneuer, Maria; Chang, Gaomei; Xu, Wendan; Augsberger, Christian; Grau, Michael; Zapukhlyak, Myroslav; Ilieva, Kristina; Landgraf, Karin; Mangelberger-Eberl, Doris; Yousefi, Kasra; Berning, Philipp; Kurz, Katrin S; et al. (Frontiers in immunology, 2023)
BACKGROUND: Despite recent advances in the treatment of aggressive lymphomas, a significant fraction of patients still succumbs to their disease. Thus, novel therapies are urgently needed. As the anti-CD20 antibody rituximab and the CD19-targeting antibody tafasitamab share distinct modes of actions, we investigated if dual-targeting of aggressive lymphoma B-cells by combining rituximab and tafasitamab might increase cytotoxic effects. METHODS: Antibody single and combination efficacy was determined investigating different modes of action including direct cytotoxicity, antibody-dependent cell-mediated cytotoxicity (ADCC) and antibody-dependent cellular phagocytosis (ADCP) in in vitro and in vivo models of aggressive B-cell lymphoma comprising diffuse large B-cell lymphoma (DLBCL) and Burkitt lymphoma (BL). RESULTS: Three different sensitivity profiles to antibody monotherapy or combination treatment were observed in in vitro models: while 1/11 cell lines was primarily sensitive to tafasitamab and 2/11 to rituximab, the combination resulted in enhanced cell death in 8/11 cell lines in at least one mode of action. Treatment with either antibody or the combination resulted in decreased expression of the oncogenic transcription factor MYC and inhibition of AKT signaling, which mirrored the cell line-specific sensitivities to direct cytotoxicity. At last, the combination resulted in a synergistic survival benefit in a PBMC-humanized Ramos NOD/SCID mouse model. CONCLUSION: This study demonstrates that the combination of tafasitamab and rituximab improves efficacy compared to single-agent treatments in models of aggressive B-cell lymphoma in vitro and in vivo.
Keywords: CD20; Rituximab; Mice, SCID; leukocyty mononukleární; tumor immunology; Lymphoma, Large B-Cell, Diffuse; tafasitamab; antibody therapy; Burkitt Lymphoma; Burkittův lymfom; rituximab; humanizované monoklonální protilátky; Antibodies, Monoclonal, Humanized; myši inbrední NOD; Animals; Leukocytes, Mononuclear; difúzní velkobuněčný B-lymfom; CD19; lymphoma; zvířata; myši SCID; myši; Mice; Mice, Inbred NOD